The impact of human behavior on QHSE management systems (2025) - OULDHENIA, Mohammed (Edelweiss Applied Science and Technology, 2025)
The objective of this study is to examine the impact of human behavior on QHSE management systems. Various studies have addressed multiple influencing factors, ranging from technology to QHSE culture. Using behavioral theory as a fundamental framework for study, identifying the factors that influence behavior will enable the implementation of a responsible approach that directly contributes to the overall effectiveness and efficiency of the QHSE system. The article begins with a review of the state of the art of various research studies throughout history to focus on the stages that have marked the evolution of QHSE management systems and to extract the factors that impact management systems. The methodology adopted classifies the research into three categories: operational, organizational, and systemic. The result is a matrix of factors summarizing the role and impact of human behavior on an organization’s performance and confirming that human beings, through their behavior, are the key factor influencing the overall performance of QHSE systems. This research not only aims to ensure control of management systems, but also provides a standardized approach adapted to the three levels of management: top management, middle management, and operators & MO within the HLS structure of management systems.